The Impacts of Board Characteristics and Size on Risk Disclosure: Evidence from Indonesian Mining Firms - Belicia Viola; Josephine Aryanto; Nany Chandra Marsetio; Retno Yuliati (Journal of Economics, Business, and Accountancy Ventura, 2022)
This study examines how board characteristics (gender, education, and age) and board size can impact corporate risk disclosure (CRD) in quantity and coverage. This research differs from previous studies because we use the newest COSO framework (2017) to measure CRD. We analyzed the data using multiple regression analysis. The results show no relationship between the composition of female directors in both CRD coverage and quantity. Board size positively affects CRD coverage and quantity, while board age negatively affects those two types of CRD. However, board education does not influence CRD quantity and coverage. This study also indicates that board size and age substantially impact the level of risk disclosure. For investors, the board's age and size become an essential consideration in investment decisions related to risk information. While policymakers in Indonesia urgently need a further discussion of the implementation of guidelines to promote higher levels of risk disclosure among firms since the difference in the basis for disclosing risk will reduce the company's competitiveness in the same industry.